Adoption of innovation and farm productivity in the Sudano-Saharan zone in Cameroon - André Dumas Tsambou; Nelson Sergeo Tagang Tene (Cogent Social Sciences)
Faced with the shocks that are disrupting the agricultural system in Sub-Saharan African countries, farmers are faced with the dual challenge of adapting to the effects of these shocks and improving their productivity. Thus, agricultural innovation is one of the adaptation strategies for improving productivity. The objective of this paper is to assess the impact of the adoption of agricultural innovations on farm productivity in the Sudano-Saharan zone of Cameroon. We use survey data from 721 farms in the North and Far North (Sudano-Sahelian zone) regions of Cameroon carried out within the framework of the project “Contrat de Désendettement et de Développement1 agrosystèmes du Nord”. These data are applied by the endogenous switching regression model, which accounts for the selectivity bias of the sample while taking into account the differential impact between farms that have adopted agricultural innovations and those that have not. The results show that the adoption of agricultural innovations significantly improves farm productivity. The effect of these farm innovation adoptions is about 646.44 kg/ha compared to those that did not adopt any innovations.